INFLUENCE OF FEEDING THREE TYPES OF DRY POULTRY MANURE ON BROILER GROWTH, FEED ‎CONSUMPTION, FEKD EFFICIENCY AND MORTALITY - A. AL-Fayadh, Hamdi (The Iraqi Journal of Veterinary Medicine, 1987)
This study was carried out to determine the feasibility of dry poultry manure (DPM) as a feed stuff. Three types of DPM were studied: 1- layer litter manure, 2- caged layer manure, 3- processed caged layer manure. Three hundred fifty one-day old broiler chicks were allocated at random into seven dietary treatments, chicks in T1 (control) were fed on ‘starter and finisher commercial diets. Chicks in T2 and 13 were fed diets supplemented with 5% and 10% layer litter manure, respectively. Chicks in T4 and T5 were fed dies contained 5% and 10% caged layer manure, respectively, while chicks in T6 and T7 were fed diets contain 5% and 10% processed caged layer manure, respectively. Body weight gain, feed consumption and feed efficiency of the chicks were not significantly influenced by feeding diets containing 5% DPM. But the inclusion of 10% DPM in the diet has significantly (P < 0.05) decreased the body weight gain and feed efficiency and increased the feed consumption and mortality.